Perlindungan Hukum Terhadap Hak Masyarakat Hukum Adat Setelah Berakhirnya Hak Guna Usaha - Urasana, Yules Moses; Laturette, Adonia Ivonne; Radjawane, Pieter (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2023)
Legal protection of the Ulayat Rights of the Customary Law Community is the highest tenure right of the customary law community covering all lands as well as those belonging to certain environmental areas. The purpose of this study is to discuss the legal protection of the rights of indigenous peoples after the expiration of the HGU. P.T Waitala in West Seram Regency. The type of research used by the author, in this paper, is Normative Juridical legal research, or doctrinal legal research, which is a legal research that uses secondary data sources. This is done by emphasizing and adhering to juridical aspects. Normative legal research is library research, namely research on secondary data. Results of the Research: Legal protection of the Rights of Indigenous Peoples, is a fundamental right that must be owned by customary law communities, which has been stated in the 1945 Constitution of the Republic of Indonesia Article 18b Paragraph (2) states that